Digital coping: How frontline workers cope with digital service encounters. (6th November 2020) - Breit, Eric; Egeland, Cathrine; Løberg, Ida B.; Røhnebæk, Maria T.
Abstract: This article addresses how frontline workers cope when dealing with digitally mediated service encounters. It draws on a qualitative study of frontline workers' experiences in an increasingly digitalised work environment in the context of employment assistance services. The material shows that digitalising service encounters leads to two overall types of change for frontline employees, and the article explores related coping responses. First, the technology leads to an increased availability of the frontline workers to the clients. This is coped with by handing over, or 'outsourcing', responsibilities to clients through digital platforms, and by reducing what is experienced as 'noise' related to incoming enquiries. Second, the technology leads to increased transparency of the service interactions, which is coped with by being careful about the content of client communications. The analysis of these changes and their related coping responses contributes to the research on digital public service encounters and highlights avenues for empirical studies and theoretical development within a topical, yet little studied, field.